Avaliação da prática de prescrição de profilaxia antibiótica pelos cirurgiões-dentistas do estado do Rio de Janeiro - Sales, Meleny Ariane da Silva (2019)
The AHA recommends the protocol of antibiotic prophylaxis before invasive dental procedures as a function of the risk of bacterial endocarditis. Due to antibiotic resistance, risks and benefits of this protocol have been discussed, which are the risk procedures and which patients are at risk of contracting bacterial endocarditis. Objective: The objective of this study was to investigate the practice and knowledge regarding the prescription of antibiotic prophylaxis by dentists in the state of Rio de Janeiro. Material and method: This crosssectional study was developed from the application of electronic questionnaires elaborated in Google Forms containing 28 questions about the use of antibiotic chemoprophylaxis in dental procedures. The link to the questionnaire was sent to 13,960 electronic addresses of dental surgeons registered with the Regional Council of Dentistry of RJ. The participants were grouped according to the time of formation (up to 7 years and more than 7 years). Statistical analysis used ttests for independent samples and Chi-square, at a significance level of 5%. Outcome: Most participants, 90.3% of the group with up to 7 years of age and 94.4% of the group formed the longest, use antibiotic prophylaxis protocol. Significant differences were found for the positive responses between the groups if the patient had undergone radiotherapy (p = 0.011), 33.9% of whom had undergone up to 7 years of follow-up and 56.3% of them for more than 7 years; (p = 0.049) 91.9% for patients up to 7 years of age and 94.4% for those who had been trained for more than 7 years. 23 drug combinations have been described as prophylactic protocol. The most frequently cited was the use of 2 g of amoxicillin given 1 h prior to the procedure, without post-intervention medication, indicated by 30.6% of those aged up to 7 years and 45.1% of those formed the longest. Conclusion: The most commonly used protocol was the one recommended by the American Academy of Cardiology. However, more than half of the participants use another type of protocol among the 23 cited, demonstrating that there is no uniformity within the dental practice.